2007
DOI: 10.2337/dc06-1426
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Assessment of Hypogonadism in Men With Type 2 Diabetes

Abstract: OBJECTIVE -The aim of our study was to assess the prevalence of clinical hypogonadism, based on both symptoms and biochemical available measures of testosterone deficiency, in men with type 2 diabetes.RESEARCH DESIGN AND METHODS -In a cross-sectional study of 355 type 2 diabetic men aged Ͼ30 years, total and bioavailable testosterone, sex hormone-binding globulin, BMI, and waist circumference were measured and free testosterone was calculated. Overt hypogonadism was defined as the presence of clinical symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
371
6
28

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(446 citation statements)
references
References 49 publications
41
371
6
28
Order By: Relevance
“…The Endocrine Society in the USA recommends the routine measurement of serum testosterone levels in patients with type 2 diabetes because of the high prevalence. 6,14 Certainly, from our data and the high prevalence in our patient population, the routine screening of all type 2 diabetic men aged 50 years and older in a setting similar to ours would appear to be advisable at first glance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Endocrine Society in the USA recommends the routine measurement of serum testosterone levels in patients with type 2 diabetes because of the high prevalence. 6,14 Certainly, from our data and the high prevalence in our patient population, the routine screening of all type 2 diabetic men aged 50 years and older in a setting similar to ours would appear to be advisable at first glance.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetic men with low testosterone levels have been found to have a high prevalence of symptoms of hypogonadism, such as erectile dysfunction, low libido and fatigability. 14,18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this notion, androgen deficiency has been associated with insulin resistance, type 2 diabetes mellitus, metabolic syndrome, and increased deposition of visceral fat. [62][63][64][65] In the TIMES2 (Testosterone Replacement In Hypogonadal Men With Either Metabolic Syndrome or Type 2 Diabetes) study, 6 to 12 months of transdermal TRT (vs placebo) significantly improved insulin resistance and glycemic control in a large randomized study of hypogonadal men with type 2 diabetes mellitus (ACCF/AHA class Ib). 66 A meta-analysis of 5 other randomized controlled trials (including 3 placebo-controlled trials) with mean follow-up of 58 weeks found that TRT was associated with a significant reduction in fasting plasma glucose levels, homeostasis model assessment of insulin resistance index, triglycerides, and WC.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…Testosterone is lower in men with the metabolic syndrome or with type 2 diabetes, in comparison to metabolically healthy men (1,2). Dysfunction of the gonadal axis is central (hypogonadotrophic hypogonadism) as gonadotropins are within the normal range.…”
Section: Introductionmentioning
confidence: 97%